Monkey Madness : The Only way is Africa - Wilson, Anna. (London : Macmillan Children's Books, 2014)
Felix is going on safari! He cannot believe his luck when Dad announces he is going on a business trip to Africa and is going to take the family too. Flo, Felix's best friend in the whole world is FURIOUS that Felix is going to see so many amazing animals without her. In order for Felix to prove his friendship, she sets him a horribly difficult task: to bring her back a BABY MONKEY!
3-6.
Keywords: Monkey -- Fiction